PENGOLAHAN LIMBAH CAIR SEPTIC TANK (SEPTAGE) MENGGUNAKAN CONTRUCTED WETLANDS - Musarofa, Musarofa (Journal of Industrial Process and Chemical Engineering (JOICHE), 2025)
Typically, septic tank liquid waste is treated conventionally at Wastewater Treatment Plants (IPLT) using technologies that involve high operational and maintenance costs as well as skilled operators. In this study, the constructed wetland method was applied to treat septic tank liquid waste using several plants, including Scirpus lacustris, Cyperus rotundus, and Cyperus papyrus. The research was conducted over 42 days at the Environmental Quality Laboratory of ITATS. The treatment process lasted 25 days, aiming to reduce the BOD, TSS, and E. coli parameters in the septic tank liquid waste. The highest average removal rates were observed in Reactor 1 using Scirpus lacustris with a contact time of 25 days, achieving 81.9% removal of BOD, 94.25% removal of TSS, and 68% removal of E. coli. For Cyperus rotundus, the removal rates were 52% for BOD, 89.5% for TSS, and 63% for E. coli. For Cyperus papyrus, the removal rates were 62.84% for BOD, 87% for TSS, and 63% for E. coli. The average removal rate of Scirpus lacustris was higher compared to the other two test plants. Thus, while Scirpus lacustris is effective in reducing BOD, TSS, and E. coli concentrations, it still does not meet the E. coli quality standards set by Permen LH No. 68 of 2016 on domestic wastewater quality.